Estudo da toxicidade de metais (Zinco e cádmio) sobre Ceriodaphnia Dubia, por multivias de exposição e recuperação biológica de descendentes - Carvalho, Marcela Merides [UNESP]; Lira, Vivian Silva [UNESP]; Watanabe, Cláudia Hitomi [UNESP]; Fracácio, Renata [UNESP] (FapUNIFESP (SciELO), 2017)
Metals are often evaluated in fresh water as dissolved solutions, assuming that the toxic effect is caused only by water (respiration and contact). However, toxicity studies in food and water, in a concomitant way, as occurs in the environment, are less discussed. In this study, zinc and cadmium toxicity was evaluated through the exposure of Ceriodaphnia dubia to contaminated food and water. The species of green algae Raphidocelis subcapitata was exposed for 96h to concentrations of Zn (0,18 and 0,27 mg.L-1) and Cd (0,001 and 0,0015 mg.L-1). The results were statistically analyzed by means of Analysis of Variance (Kruskal-Wallis). Algae were used as food source for C. dubia, during chronic exposure (eight days) in the same concentrations described. Subsequently, neonates (F1 generation) were introduced in non-contaminated water and food in order to ascertain their biological recovery capacity. The number of newborns by individuals, morphology of newborns, and quantification of metals in biological tissue were evaluated. The results showed that the tested concentrations did not inhibit the growth of R. subcapitata, while C. dubia had chronic toxicity, with reduction in the reproductive rate in both generations, for both metals. The results allowed the conclusion that, even at relatively low concentrations, the metals zinc and cadmium can alter the reproductive patterns of freshwater invertebrates, compromising the aquatic ecosystem and its resilience. Thus, considering the toxic effects of these metals and their interference in the biological system, new ecotoxicological tests should be performed to allow a better understanding of the behavior of these substances in organisms.
Study of metals toxicity (Zinc and cadmium) to ceriodaphnia Dubia, for multi-exposition and biological recovery of offspring
Keywords: Ceriodaphnia dubia; Generations; Metals; Raphidocelis subcapitata; Toxicity